Crystalline and thermal properties in miscible blends of PEEK, PPS and PEI obtained by melt compounding - Chen Jian-bing; Guo Wen-he; Li Zhun-zhun; Tian Li-ming (Functional Materials, 2016)
The effects of crystal and amorphous polymers on the structure, morphology, crystalline and thermal properties of PEEK have been investigated by using FT-IR, SEM, DSC and TGA. The interaction existing in PEEK/PPS and PEEK/PEI alloys was stronger than that in PEEK/PPS/PEI alloys. The SEM results revealed that homogeneous structure exists in the alloys of PEEK/PPS, PEEK/PEI and PEEK/PPS/PEI. All of the binary and ternary alloys based PEEK exhibits single glass transition temperature (Tg) in full composition range. When PEI was added to the PEEK/PPS alloys, the Tg of PEEK/PPS/PEI alloys increased from 146 °C to 179 °C. The crystallinity degree of PEEK increased when PPS was added, and decreased as PEI added. The crystallization peak of PEEK/PPS/PEI alloy disappears in the ratio of 50/25/25. The thermal decomposition temperature (Td5%) of PEEK/PPS and PEEK/PEI alloys decreased when PPS and PEI were added, the Td of PEEK/PPS/PEI alloy in the ratio of 70/15/15 presented at 510 °C, which was lower than pure PEEK and pure PEI, higher than PPS.